2014
DOI: 10.1155/2014/904834
|View full text |Cite
|
Sign up to set email alerts
|

Salidroside Stimulates Mitochondrial Biogenesis and Protects against H2O2-Induced Endothelial Dysfunction

Abstract: Salidroside (SAL) is an active component of Rhodiola rosea with documented antioxidative properties. The purpose of this study is to explore the mechanism of the protective effect of SAL on hydrogen peroxide- (H2O2-) induced endothelial dysfunction. Pretreatment of the human umbilical vein endothelial cells (HUVECs) with SAL significantly reduced the cytotoxicity brought by H2O2. Functional studies on the rat aortas found that SAL rescued the endothelium-dependent relaxation and reduced superoxide anion (O2∙−)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 79 publications
5
47
0
Order By: Relevance
“…These pro-inflammatory genes facilitate monocyte-endothelial cells interactions and initiate early stages of atherosclerosis. Many evidences have revealed that H 2 O 2 can cause endothelial cells activation and induce adhesion molecules and chemokines expression in vitro(Xing et al, 2014). Here, we demonstrate for the first time that β-elemene can directly regulate the expression of adhesion molecules (ICAM-1 and VCAM-1).…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…These pro-inflammatory genes facilitate monocyte-endothelial cells interactions and initiate early stages of atherosclerosis. Many evidences have revealed that H 2 O 2 can cause endothelial cells activation and induce adhesion molecules and chemokines expression in vitro(Xing et al, 2014). Here, we demonstrate for the first time that β-elemene can directly regulate the expression of adhesion molecules (ICAM-1 and VCAM-1).…”
mentioning
confidence: 54%
“…Briefly, OH · was generated by the Fenton reaction and treated with a chromogenic substrate nitrotetrazolium blue chloride (NBT) to yield a stable colored substance, which was measured at 450 nm. The reaction product of H 2 O 2 and molybdic acid was determined at 405 nm using the fluorescence microplate reader (Xing et al, 2014) …”
Section: Detection Of Oh · and H 2 O 2 In Huvecsmentioning
confidence: 99%
“…Preparations of R. rosea or salidroside protect against oxidative damage caused by hydrogen peroxide in numerous experimental systems involving different cell types, including human neuroblastoma cells (SH-SY5Y and IMR-32) (Zhang et al 2007;Schriner et al 2009), human osteosarcoma cells (Schriner et al 2009), human fetal lung fibroblasts (Mao et al 2010), human hepatocytes (Guan et al 2011b), human cortical neurons (HCN 1-A) (Palumbo et al 2012), human endothelial and endothelial progenitor cells (Xu et al 2013;Zhao et al 2013;Tang et al 2014;Xing et al 2014), rat pheochromocytoma cells (PC12) (Cai et al 2008), primary cultured rat hippocampal and cortical neurons (Chen et al 2009;Shi et al 2012), and rat cardiomyoblasts (H9c2) (Zhu et al 2011). …”
Section: Phytochemical Composition Of Rhodiola Roseamentioning
confidence: 99%
“…Starting and it improves memory (17)(18)(19). Studies have indicated that salidroside alleviates hydrogen peroxideinduced endothelial injury by improving mitochondrial activity (20) and it improves microcirculation (21). Thus, salidroside has been used to treat high-altitude erythrocytosis.…”
Section: Pharmacological Research and Its Clinical Application: Statumentioning
confidence: 99%